KNOWLEDGE-BASED SYSTEM OF AUTISM SPECTRUM DISORDER IN EARLY CHILDHOOD - Silmi Hamidah; Kiki Kusumawati (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2023)
Autism sufferers that occur in early childhood not only those who have physical abnormalities, even many of them who suffer from autism physical appearance perfect, but when consulted to experts are diagnosed with autism. There is also a parent not knowing that their child has autism because they do not have knowledge about Autism itself. With this knowledge-based system that is part of artificial intelligence that studies how to adopt the way an expert thinks and reason in solving a problem. In this research will be designed a knowledge-based system to diagnose Autism Spectrum Disorder disorder. By applying knowledge-based system with intermediary media this system is made by using PHP programming language and MySQL database. The reasoning of this knowledge based system application uses advanced inference or ForwardChaining techniques. Where in forward chaining begins with initial information as part of the initial symptoms and moves forward to match the next information to find the information in accordance with the rules, then will conclude in the form of information types Autism Spectrum Disorder disorder and solutions in the form of therapy in accordance with the advice of child psychologists. Using the Best First Search technique in the process for conclusions or the final consultation. This system can be accessed whenever and wherever they are or parents who children with symptoms have grouped into the Autism Spectrum Disorder section.